Fabrication of multifilamentary powder in tube superconducting tapes of Bi-2223 with Sr deficient starting composition. (March 2021) - Zhang, Shengnan; Ma, Xiaobo; Shao, Botao; Cui, Lijun; Liu, Guoqing; Zheng, Huiling; Liu, Xueqian; Feng, Jianqing; Li, Chengshan; Zhang, Pingxiang
Highlights: Bi-2223 multifilamentary tapes with high current capacity have been fabricated. Obvious influence of Sr deficiency on Bi-2223 tapes on the thermodynamic properties. Systematical change of Bi-2223 superconductivity with Sr content. Abstract: Bi2 Sr x Ca2 Cu3 O10+δ (Bi-2223) precursor powders were fabricated by co-precipitation process with different Sr content of x = 1.93, 1.90, and 1.85. Multi-filamentary Bi-2223 high temperature superconducting tapes were fabricated by the traditional powder in tube process (PIT) with different precursor powders. The influences of Sr content on the phase formation dynamics as well as the superconducting properties of Bi-2223 tapes have been systematically investigated. With decreasing Sr content, the critical temperature of Bi-2223 tapes decreased from 109.9 K to 107.7 K, which implied that the change of Sr content could change the carrier concentration on Cu-O plane, thus led to the variation of intrinsic superconducting transition behavior. Besides, with the decrease of Sr content, the phase formation temperature decreased. Bi-2223 tapes with higher superconducting phase content were obtained with the Sr content of 1.85, which was beneficial to the improvement of intergrain connections. Thus, the J c - B behavior was enhanced under the magnetic field parallel to the ab plane of Bi-2223. With further optimization of sintering process, the maximum I c of 128 A was achieved on Sr = 1.85 tape, corresponding to the critical current density, J c of 25.8 kAcm −2 .